2019
DOI: 10.1103/physrevb.100.024101
|View full text |Cite
|
Sign up to set email alerts
|

Polar nature of domain boundaries in purely ferroelastic Pb3(PO4)2 investigate

Abstract: Domain boundaries in lead phosphate, Pb 3 (PO 4) 2 , are investigated by using second harmonic generation (SHG) microscopy. It is revealed that they are polar while the bulk is a purely ferroelastic, centrosymmetric material. Pb 3 (PO 4) 2 contains W and W walls with different orientations. The SHG microscopy shows that both W and W walls are polar, in striking contrast to the bulk, where the macroscopic polarity is forbidden by symmetry. The strongest polarity is observed in the W walls with a local symmetry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 56 publications
2
16
0
Order By: Relevance
“…BiVO4 is almost the same as with other ferroelastic materials [19][20][21][22] , and it is around 10 -8 weaker than in normal ferroelectrics, which produce SH signals from the bulk. Except for ferroelastic domain boundaries, no SH signals are detected from the bulk region in BiVO4.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…BiVO4 is almost the same as with other ferroelastic materials [19][20][21][22] , and it is around 10 -8 weaker than in normal ferroelectrics, which produce SH signals from the bulk. Except for ferroelastic domain boundaries, no SH signals are detected from the bulk region in BiVO4.…”
mentioning
confidence: 80%
“…For example, in CaTiO3 and Pb3(PO4)2 19,22 , we observed that the orientations of SH maxima are slightly different for each domain boundary, especially when the density of domain boundaries is high. We believe that the static interaction between polar domain boundaries plays some contribution in this phenomena.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…These switches are largely athermal because the energy barriers between different domain states are usually much greater than the thermal energy. It was shown that ferroelastic domain boundaries are generally polar [19][20][21][22][23][24][25]. The first example was CaTiO 3 [19] where polarity was observed in transmission electron microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Ferroelastic materials are defined by their ferroelastic hysteresis 1 in analogy with ferroelectric and ferromagnetic materials and their relevant hysteresis behavior. Additional ferroic properties often emerge when ferroelastic materials show polarity inside their domain boundaries while no such polarity exists in their bulk 214 . Non-polar bulk materials like SrTiO 3 and LaAlO 3 show strong local dipoles inside twin walls 1520 .…”
Section: Introductionmentioning
confidence: 99%